ANALISIS PENGARUH PREFERENSI MEREK, PERSEPSI KUALITAS, DAN PERCEIVED VALUE TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR YAMAHA MATIK DI SEMARANG - Imroatul Khasanah (JURNAL STUDI MANAJEMEN ORGANISASI, 2017)
This research study aimed to determine the influence of brand preference,perceivedquality, Perceived Value toward purchasing decisions. This research is motivatedincreasingly tight competition level of automatic motor cycle. A sample of this study is100 consumens. The technique used in sampling is an accidental sampling. The results ofthis study is a manufacture company or business actors which is able to offer the benefitthrough increased brand preference by providing added value services to business andconsumers, will eventually be able to influence its consumer behaviour in purchasingdecisions.Key words: brand preference , perceived quality, Perceived Value , purchase decisions.